Development of E-Physics Teaching Material Integrated with Augmented Reality and Ethno-Meaningful Learning to Promote Students’ 21st Century Skills - Rima Melani Putri; Asrizal; Mutiara Nurul Fitri (Postgraduate, University of Mataram, 2025)
This study aims to determine the need analysis, validity, and practicality of e-physics teaching material integrated with augmented reality and ethno-meaningful learning to promote students’ 21st century skills. The research used a development method based on the Plomp model, and data were analyzed using descriptive statistics. The needs analysis showed that students' 21st-century skills scored 56.59 out of 100, which falls in the very low category. Context analysis of existing physics teaching material, integration of ethnoscience, meaningful learning, and the difficulty level of heat material yielded scores of 50.00, 34.16, 59.44, and 48.22 respectively, indicating low to very low readiness for current implementation. The content validity of the developed teaching material, assessed using Aiken’s V, reached 0.78, indicating it is valid. Its practicality score, based on responses from teachers and students, was 87.00 out of 100, categorized as very practical. The findings indicate that the developed e-physics teaching materials are needed, valid, and practical, and are suitable for supporting the physics learning process. However, further studies are required to evaluate their effectiveness in improving 21st-century skills.